KEMAMPUAN PENGGUNAAN TSUYOI DAN JOUBU MAHASISWA TAHUN MASUK 2021 PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - Rahmatika, Idria; Arni, Rita (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
This research is motivated by the difficulty that students face in understanding the use of "Tsuyoi" and "Joubu," which have similar meanings but different nuances in Japanese sentences. The aim of this study is to determine the proficiency of "Tsuyoi" and "Joubu" among students who entered the Japanese Language Education Program at Universitas Negeri Padang in 2021. The research employed a quantitative approach with a descriptive method, using numerical data in the form of scores. The population consisted of 53 students who entered the Japanese Language Education Program at Universitas Negeri Padang in 2021. The sample was selected using purposive sampling. The data collected for this study were the scores from tests assessing the students' proficiency in using "Tsuyoi" and "Joubu." Based on the results of the conducted research, the following conclusions can be drawn. Firstly, the overall proficiency in using "Tsuyoi" and "Joubu" is categorized as 'insufficient,' with an average score of 53.54. Secondly, in terms of Tsuyoi proficiency, students are able to correctly place "Tsuyoi" in Japanese sentences, qualifying as "sufficient" with an average score of 56.08. Thirdly, in terms of Joubu proficiency, students' ability to correctly place "Joubu" in Japanese sentences is categorized as "insufficient," with an average score of 53.54.